2015
DOI: 10.1101/gr.193607.115
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide annotation of microRNA primary transcript structures reveals novel regulatory mechanisms

Abstract: Precise regulation of microRNA (miRNA) expression is critical for diverse physiologic and pathophysiologic processes. Nevertheless, elucidation of the mechanisms through which miRNA expression is regulated has been greatly hindered by the incomplete annotation of primary miRNA (pri-miRNA) transcripts. While a subset of miRNAs are hosted in protein-coding genes, the majority of pri-miRNAs are transcribed as poorly characterized noncoding RNAs that are 10's to 100's of kilobases in length and low in abundance du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
95
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 42 publications
12
95
0
1
Order By: Relevance
“…The correlation was substantially higher for highly differentially expressed miRNAs (average Spearman r = 0.59; n = 159; P = 1 × 10 −35 , Mann-Whitney U test, one-sided), and exceeded correlations found for previously published 14,3335 miRNA promoter annotations (Figure S20d). About 11% of pri-miRNAs in human were polycistronic, containing multiple mature miRNAs with highly correlated expression levels (average Spearman r = 0.74; n = 1,372; P < 10 −100 , Mann-Whitney U test, one-sided) (Figure 3d and S28).…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…The correlation was substantially higher for highly differentially expressed miRNAs (average Spearman r = 0.59; n = 159; P = 1 × 10 −35 , Mann-Whitney U test, one-sided), and exceeded correlations found for previously published 14,3335 miRNA promoter annotations (Figure S20d). About 11% of pri-miRNAs in human were polycistronic, containing multiple mature miRNAs with highly correlated expression levels (average Spearman r = 0.74; n = 1,372; P < 10 −100 , Mann-Whitney U test, one-sided) (Figure 3d and S28).…”
Section: Resultsmentioning
confidence: 59%
“…RACE experiments confirmed that the transcripts generated at the identified promoter extended to the mature miRNA for 6 out of 7 miRNAs (Figure S21, Table S18). RNA-seq data 14 of cells expressing a dominant-negative Drosha protein provided additional evidence for the FANTOM5 annotated pri-miRNAs, with 483 out of 607 pri-miRNAs (80%) having a 5′ end within 300 base pairs of an RNA-seq transcript assembly extending to the mature miRNA locus (Figure S22). …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…HepG2) published by the Mendell laboratory (Chang et al 2015), as well as publicly available mature miRNA sequencing data from other laboratories (Bogerd et al 2014;Cao et al 2016;Hannafon et al 2016). By examining miRNAs with a higher mature-to-primiRNA ratio versus those with a lower ratio, we observed significant enrichment for optimal stem length or CNNC, and a stronger enrichment when both features were present (Supplemental Fig.…”
Section: Bulge Positions Control Hairpin Processingmentioning
confidence: 78%